Informational support for families of children with autism spectrum disorder - Gisele Weissheimer; Verônica de Azevedo Mazza; Cibelly Aliny Siqueira Lima Freitas; Silvana Rodrigues da Silva (Universidade Federal do Rio Grande do Sul, 2021)
ABSTRACT Objective: To identify the sources of informational support used by families of children with Autism Spectrum Disorder. Method: Qualitative and descriptive research carried out in three health institutions and three teaching institutions in Paraná, Ceará and Amapá. 55 family members participated who responded to semi-structured interviews, between September 2018 and 2019. Thematic categorical analysis and the resources of Qualitative Data Analysis Software were used. Results: Families find informational support from several sources, both formal and informal, such as the internet and other sources (books, Workshops, courses, television). Conclusion: Families use different sources of information, however, often incomplete and contradictory, which can generate a new demand on health professionals, in order to integrate access to information in the health care process, since they must be considering benefits and weaknesses that this represents for society.